Evaluating the potential of solar energy and its role in supporting the infrastructure services at Trebil border complex in Anbar Governorate - Omar Ali Hammad , Dr.Nather Sabbar Hamad Al-Mehemdy (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study area has a large abundance of renewable energy sources, especially solar radiation, so it must be invested in supporting the anchor structures services in the Trebil Border Complex, and for this reason, the analytical - quantitative approach was used as well as meteorological data for solar radiation, wind and rain, and the research found that a complex Trebil boundary needs electrical energy up to (1215464) watts / hour / day equivalent to (1215.464) kilowatt hours. To meet this need, the research suggested a solar system because the stations in the study area have a very large solar flood, and the capacity of that system has reached (1225) A kilowatt / hour by (3500) solar panels with an area of (8000-10000) square meters and a cost of (1225000) dollars at a cost of (1) dollars per watt, with internal street lighting And surveillance cameras, solar heaters, desalination plants, and more than the complex needs, through which the areas near it are fed, especially the Rutba district.